Strategy of managing knowledge in organizations / Raja Abdullah Yaacob, Hazeman Ahmad and Raja Ahmad Iskandar - Yaacob, Raja Abdullah; Ahmad, Hazeman; Iskandar, Raja Ahmad (Faculty of Information Management, 2013)
In organizations, knowledge can be beneficial in the business process by save costs and time. Organization needs to understand its business, its mission and vision before strategy can be made. Increasing number of organizations have recognized the need for systematically managing knowledge, hence the application of knowledge management in their management system. This paper identifies and discusses the important of mission and vision to generate strategies and what strategy should be used for organizations to manage knowledge with some case studies.